Schultereckgelenkverletzung Typ III – eine Herausforderung auch für die Physiotherapie! - Rucker, Alfred M.L.; Clijsen, Ron; Cabri, Jan (Sportverletzung · Sportschaden, 2011)
Introduction: The management of type III acromioclavicular joint dislocations, originally classified by Rockwood and Tossy, is still controversial. Purpose of this literature research was to evaluate the rehabilitation success of type III injury after conservative versus operative treatment concerning strength, function and pain of the shoulder. The objective of the study was to review the pros and cons of operative versus conservative treatment. Method: Relevant studies were collected by conducting a literature search using the online databases; the selection criteria were: randomized trials, clinical trials, review articles, and metaanalyses. A total of 10 papers published between 1998 and 2009 were selected and compromised 6 reviews and 4 clinically controlled studies. The analysis and comparison followed the criteria of evidence-based medicine. Results: The research showed no significant superiority of neither operative nor conservative treatment although the majority of the paper’s authors seem to recommend conservative intervention. Minimal differences in outcomes concerning strength, function and pain of the shoulder justify this decision. Several reasons such as the common risks of surgery, a bigger effort and explicitly higher costs only to name some seem to be unacceptable for the possible case of minimally better outcome. The analysis and interpretation of the given studies launched a discussion about the comparability of over 150 different surgical techniques, insufficiently defined approaches of conservative treatment, differences in gender concerning recuperation, validity of measuring equipment, long term and short term results of the particular methods. Discussion: At the current state of knowledge there is no gold standard for the treatment of type III acromioclavicular dislocations. To reach a consensus on which intervention should initially be chosen interventions have to respect the factors mentioned above while creating new clinically controlled studies. Furthermore, the lack of guidelines for a conservative approach constitutes a challenge for future findings regarding physical therapy.
Keywords: Introduction; Method; Results; Discussion